Construction of The Concept of Religious Moderation Institut Agama Islam Negeri Curup - Sahib, Abdul; Harmi, Hendra; Putra, Alven (AJIS: Academic Journal of Islamic Studies, 2024)
This study aims to analyze the construction of the concept of religious moderation at IAIN Curup based on the perspectives of the academic community, religious leaders and community leaders of Rejang Lebong. This type of research is descriptive qualitative research. This research was conducted in October 2021 with research instruments in the form of questionnaire sheets, observation sheets, and interview sheets. The population taken in this study is the entire academic community of IAIN Curup and all religious and community leaders of Rejang Lebong. From the entire population, a sample of 200 people who are the academic community and 22 people who are religious leaders and community leaders of Rejang Lebong are taken. Sampling using purposive sampling technique. The results of this study indicate that the concept of religious moderation in IAIN Curup is returned to their respective lecturers through course licensing, maybe not 100% but the concept of religious moderation at IAIN Curup is still being pursued. Empirical experience of religious moderation at IAIN Curup has been felt starting from internal activities on campus as well as external activities in collaboration with parties outside the campus. The first strategy for implementing religious moderation in IAIN Curup is licensing in certain subjects and lecturer workshops, research on religious moderation, and thematic Community Service and Community Service. The understanding of religious moderation from the academic community, community leaders and religious leaders of Rejang Lebong is good. The direction of developing religious moderation within IAIN Curup by making activities from Real Work Lectures (KKN), lectures, research and others has the aim of leading to religious moderation. For further research on the construction of religious moderation in the IAIN Curup environment, it can be taken from even more perspectives.Â